2004
DOI: 10.1051/0004-6361:20035751
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic monitoring of the transition phase in nova V4745 Sgr

Abstract: Abstract. We present a spectroscopic monitoring of the transient nova V4745 Sagittarii (Nova Sgr 2003 #1) covering ten months after its discovery. During this period the light curve showed a well expressed transient phase in the form of six rebrightenings, and the presented dataset is one of the best spectroscopic coverages of a classical nova during the transition phase. Low-and medium-resolution spectra revealed that the majority of spectral lines switched back to strong P-Cyg profiles during the mini-outbur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 33 publications
(37 reference statements)
6
33
0
Order By: Relevance
“…This means that the intervals between consecutive maxima get gradually longer, as was noted for this nova by Csák et al (2005). V2540 Oph and DK Lac apparently exhibit the same behavior.…”
Section: Long-term Behavior Of the Flaressupporting
confidence: 74%
See 2 more Smart Citations
“…This means that the intervals between consecutive maxima get gradually longer, as was noted for this nova by Csák et al (2005). V2540 Oph and DK Lac apparently exhibit the same behavior.…”
Section: Long-term Behavior Of the Flaressupporting
confidence: 74%
“…They spectroscopically monitored the transition phase of V4745 Sgr and found that during the rebrightenings the continuum emission rose and that the spectral lines showed P-Cyg profiles, which suggests a temporary increase in massloss rate. On the basis of these observations, Csák et al (2005) suggested that the rebrightenings are envelope-hydrogenburning instabilities. They also observed a gradual increase of the time intervals between rebrightenings, which was also noted previously in GK Per and DK Lac by Bianchini et al (1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that the accretion disk is recovered around the same time the transition phase occurs supports a connection between the two phenomena. Csák et al (2005) found that spectra obtained during the maxima of the oscillations in the transition phase of V4745 Sgr are similar to spectra taken just after its nova eruption in 2003. Therefore, they proposed to explain the oscillations by several episodes of mass ejection, which they called ''mini nova-outbursts.''…”
Section: The Transition Phase In Novaementioning
confidence: 60%
“…it was not an hybrid nova, and its emission lines were twice as wide as in V5588 Sgr. In addition, while the spectra of V5588 Sgr did not change during SdM other than for the appearance of the weak broad pedestal, the emission lines of V4745 Sgr during SdM switched back to strong P-Cyg absorption profiles as for the primary maximum (Csák et al 2005, Tanaka et al 2011.…”
Section: Discussionmentioning
confidence: 92%